Status Quo of City Logistics in Scientific Literature: Systematic Review - Wolpert, Stefan; Reuter, Carsten (Transportation Research Record, 2012)
Roadway infrastructure is reaching maximum capacity in urban areas because of expanding urbanization, demographic changes, and continuously increasing freight volumes. An overview of the latest research on city logistics is needed to address these challenges, and a review of the scientific literature is presented. A specifically designed framework for systematic literature review was used to analyze 92 relevant articles from prominent electronic databases. A taxonomy of city logistics literature was created to aid academics and practitioners and to stimulate interest of other parties in this area.<br

Technology as a service enabler in retail environments. - Wolpert, Stefan; Roth, Angela (26th Annual Reser Conference, 2016)
The brick and mortar retail environment is currently under transition due to potential new technological innovations. The purpose of this paper is to classify and organize the accumulated knowledge about technology based retail services (TBRS) as revealed in the scientific literature. This paper presents a systematic and comprehensive review of major literature on TBRS. This study was conducted in Elsevier Scopus and led to a sample of 67 peer-reviewed articles published between 2003 and 2016 worldwide. Altogether, 32 different TBRS were identified. As far as the authors are aware, this paper provides the first systematic review of TBRS literature, which not only helps to organize retail based services but also identifies seven basic technologies underlying current TBRS.